Placental Mitochondrial DNA Content and Particulate Air Pollution during in Utero Life - Janssen, Bram G. (National Institute of Environmental Health Sciences, 2012)
Background: Studies emphasize the importance of particulate matter (PM) in the formation of reactive oxygen species and inflammation. We hypothesized that these processes can influence mitochondrial function of the placenta and fetus. Objective: We investigated the influence of PM(10) exposure during pregnancy on the mitochondrial DNA content (mtDNA content) of the placenta and umbilical cord blood. Methods: DNA was extracted from placental tissue (n = 174) and umbilical cord leukocytes (n = 176). Relative mtDNA copy numbers (i.e., mtDNA content) were determined by real-time polymerase chain reaction. Multiple regression models were used to link mtDNA content and in utero exposure to PM(10) over various time windows during pregnancy. Results: In multivariate-adjusted analysis, a 10-µg/m³ increase in PM(10) exposure during the last month of pregnancy was associated with a 16.1% decrease [95% confidence interval (CI): –25.2, –6.0%, p = 0.003] in placental mtDNA content. The corresponding effect size for average PM(10) exposure during the third trimester was 17.4% (95% CI: –31.8, –0.1%, p = 0.05). Furthermore, we found that each doubling in residential distance to major roads was associated with an increase in placental mtDNA content of 4.0% (95% CI: 0.4, 7.8%, p = 0.03). No association was found between cord blood mtDNA content and PM(10) exposure. Conclusions: Prenatal PM(10) exposure was associated with placental mitochondrial alterations, which may both reflect and intensify oxidative stress production. The potential health consequences of decreased placental mtDNA content in early life must be further elucidated.